Pen for a party : Dryden's Tory propaganda in its contexts - Harth, Phillip, 1926- (Princeton legacy library., 1993)
Exploring the political climate during the final years of the reign of Charles II, when John Dryden wrote his great public poems and several of his dramatic works, Phillip Harth sheds new light on this writer's literary activity on behalf of the monarch. The poems Absalom and Achitophel and The Medall, and the dramatic works The Duke of Guise and Albion and Albanius, have commonly been considered in relation to such public events as the Popish Plot, the Exclusion Crisis, and the Tory Reaction, but that approach does not explain the noticeable differences among these works or the specific purp.